Skull Base Repair following Resection of Vestibular Schwannoma: A Systematic Review (Part 1: The Retrosigmoid Approach) - Starup-Hansen, Joachim; Williams, Simon C.; Valetopoulou, Alexandra; Khan, Danyal Z.; Horsfall, Hugo Layard; Moudgil-Joshi, Jigishaa; Burton, Oliver; Kanona, Hala; Saeed, Shakeel R.; Muirhead, William; Marcus, Hani J.; Grover, Patrick (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objective Despite advances in skull-base reconstruction techniques, cerebrospinal fluid (CSF) leaks remain a common complication following retrosigmoid (RS) vestibular schwannoma (VS) surgery. We aimed to review and classify the available strategies used to prevent CSF leaks following RS VS surgery.Methods A systematic review, including studies of adults undergoing RS VS surgery since 2000, was conducted. Repair protocols were synthesized into a narrative summary, and a taxonomic classification of techniques and materials was produced. Additionally, the advantages, disadvantages, and associated CSF leak rates of different repair protocols were described.Results All 42 studies were case series, of which 34 were retrospective, and eight were prospective. Repair strategies included heterogeneous combinations of autografts, xenografts, and synthetic materials. A repair taxonomy was produced considering seven distinct stages to CSF leak prevention, including intraoperative approaches to the dura, internal auditory canal (IAC), air cells, RS bony defect, extracranial soft tissue, postoperative dressings, and CSF diversion. Notably, there was significant heterogeneity among institutions, particularly in the dural and IAC stages. The median postoperative incidence of CSF leaks was 6.3% (IQR: 1.3–8.44%).Conclusions The intraoperative strategies used to prevent CSF leaks during RS VS surgery vary between and within institutions. As a result of this heterogeneity and inconsistent reporting of CSF leak predictive factors, a meaningful comparative analysis of repair protocols was not feasible. Instead, we propose the development of a prospective multicenter observational evaluation designed to accurately capture a comprehensive dataset of potential CSF risk factors, including all stages of the operative repair protocol.
Keywords: vestibular schwannoma; CSF leak; skull base repair; neurosurgery; ear nose and throat; retrosigmoid approach